Constitutional Interpretation - Sánchez Sánchez, Abraham (EUNOMÍA. Revista en Cultura de la Legalidad, 2017)
This article presents a general view of constitutional interpretation based on the main topics that are being discussed currently. First, to be an object of interpretation, the Constitution needs a written document endowed with normative character. Hereafter we conduct a review of the material content of the current Constitutions, the indetermination of it articles and the role of conventional methods of constitutional interpretation. In addition, it deals with the agents of constitutional interpretation, paying attention to the legislature and the Constitutional Courts. The latter, due to its position of supreme interpreters of the Constitution, has direct and constant contact with the ordinary judiciary and the legislature. This Constitutional Court-legislature relation is particularly problematic because it contains a tension between two concepts: Constitution and Democracy. Finally, the paper remarks the risks associated with constitutional interpretation which affects its written and normative character, the two main requirements that make constitutional interpretation possible.